(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
This paper provides a review of the hydroclima- tic variability reconstructions along the subtropical Argentinean region based on paleolimnological re- cords from Laguna Mar Chiquita (Córdoba; Piovano et al., 2002, 2004, 2009), Laguna Melincué (Santa Fe; Guerra, 2015; Guerra et al., 2015) to Lagunas Encadenadas del Oeste (LEO; Buenos Aires; Córdoba, 2012; Fig. 1). Lake records span two climatologically interesting periods, the so-called Little Ice Age (LIA; Grove, 2001; Wanner et al., 2008) and the 20th century. Regional climate in the studied area is mainly defined by the South American Monsoon System that rules the precipitation regime and is one of the major atmospheric features driving seasonal climatic variability in southeastern South America (Vera et al., 2006; Garreaud et al., 2009; Carvalho et al., 2011; Fig. 1). The need for an integral analysis of the high (1-101 years) and low (>102 years) frequency hydroclimatic variability associated with the South American Monsoon System activity becomes relevant when considering the significant “hydroclimatic jump” occurred during mid-1970s in the southeast of South America (Castañeda and Barros, 1994; Boulanger et al., 2005; Piovano et al., 2009; Carvalho et al., 2011; Jacques-Coper and Garreaud, 2014). This “jump” toward humid conditions (Figs. 2, 3) has been recorded as one of the largest instrumentally recorded hydrological changes occurred globally in continental environments (Giorgi, 2002). Because some climate variability patterns are characterized by long periods, it is difficult to distinguish whether the observed environmental variability is natural or corresponds to a climatic change with multiple forcing factors (natural plus anthropogenic). In this sense hydroclimatic reconstructions based on mul- tiple proxies (sedimentology, geochemistry, biomar- kers, stable isotopes) provide insight into how was environmental variability during a longer period than that perceived by the people of an affected region. Results of instrumental data blended with multi- proxy studies on sedimentary cores from Laguna Mar Chiquita (Fig. 5), Laguna Melincué (Fig. 6) and Lagunas Encadenadas del Oeste (Fig. 7) indicate that Pampean lake systems have clearly recorded hydrological variations around the end of the LIA (since AD 1770) to the present. Sedimentological, geochemical and isotopic data (Figs. 5, 6 and 7) combined with robust chronologies based on 210Pb profiles (Fig. 4) and historical data (Piovano et al., 2002, 2004; Guerra, 2015; Guerra et al., 2015; Córdoba, 2012; Córdoba et al., en revisión) provide the framework for building a sedimentary model for Pampean shallow lakes with highly variable water depth and salinity (Fig. 8). Intervals with either negative or positive hydrological balances control lake water levels, salinity and primary productivity, and also the isotopic composition of both authigenic carbonate (d18Ocarb and d13Ccarb) and sedimentary organic matter (d13Com). Extensive evaporation during lowstand stages results in an enrichment of 18O and 13C in the lake waters, and is recorded in the sediments as the most positive d18Ocarb and d13Ccarb compositions. Conversely, more negative d18Ocarb and d13Ccarb values are the result of increasing freshwater input into the lake system. Relatively low d13Com values correspond with high lake levels, low salinity, low alkalinity and high lake productivity. High water salinity during lowstands diminishes the amount of primary production and the d13Com value is correspondingly high. Lake water level drops and concurrent increases in salinity promoted the development of evaporitic layers and a marked decrease in primary productivity. The deposits of these dry stages are evaporite-bearing sediments with a low organic matter content. Conversely, highstands are recorded as organic matter-rich muds. These results show that Pampean lakes are good sensors of high- and low-frequency changes in the recent hydrological budget and, therefore, document climatic changes at middle latitudes in south-eastern South America. The paleohydrological reconstructions based on these Pampean lacustrine sedimentary sequences (Figs. 5, 6 and 7) allowed identifying three major environmental periods (Fig. 9). The paleolimnologi- cal records indicate that during the end of the LIA arid conditions prevailed along the Pampean region, reflected by low to extremely shallow-water depths, with shorter intermediate lake-level phases (Period III; Fig. 9). The LIA would have extended until AD 1870/1880, as indicated by the passage from ephemeral to perennial lake systems. From ca. AD 1870/1880 to 1976/1977 a progressive climate improvement after a sustained increase in effective moisture occurred along the region, reflected by the intermediate lake levels achieved since the second half of the nineteenth century (Period II; Fig. 9). During the last 40 years the highest lake levels of the analyzed period were established, leading to the development of the present-day hydrological conditions (Period I). These results allow improving the models based on past hydroclimatic variability in areas located east-southeast of American Arid Diagonal (Bruniard, 1982; Piovano et al., 2009), and provide critical information to decipher South American Monsoon System activity in its southernmost influence area.